Dynamic Analysis of a Quarter Car Model Moving Over a Gaussian Bump - Paliwal, Vipul; Dobriyal, Ritvik; Kumar, Pushpendra (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*289.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.87449);" role="presentation">Suspension <span dir="ltr" style="left: calc(var(--scale-factor)*121.46px); top: calc(var(--scale-factor)*289.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.920826);" role="presentation">systems have always been an <span dir="ltr" style="left: calc(var(--scale-factor)*247.85px); top: calc(var(--scale-factor)*289.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.96663);" role="presentation">important part of consid<span dir="ltr" style="left: calc(var(--scale-factor)*348.67px); top: calc(var(--scale-factor)*289.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.955505);" role="presentation">eration in automobile <span dir="ltr" style="left: calc(var(--scale-factor)*441.22px); top: calc(var(--scale-factor)*289.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.945593);" role="presentation">considering the ride <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*302.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.926352);" role="presentation">comfort and passenger safety. <span dir="ltr" style="left: calc(var(--scale-factor)*199.61px); top: calc(var(--scale-factor)*302.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.970958);" role="presentation">A modern vehicle utilizes <span dir="ltr" style="left: calc(var(--scale-factor)*310.63px); top: calc(var(--scale-factor)*302.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.880648);" role="presentation">advanc<span dir="ltr" style="left: calc(var(--scale-factor)*338.95px); top: calc(var(--scale-factor)*302.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.919534);" role="presentation">ed suspension systems and therefore various <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*315.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.950281);" role="presentation">studies regarding quarter car suspension analysis have been done. The present work <span dir="ltr" style="left: calc(var(--scale-factor)*434.38px); top: calc(var(--scale-factor)*315.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.968589);" role="presentation">on quarter car model <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*329.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.935614);" role="presentation">passing over a Gaussian bump is <span dir="ltr" style="left: calc(var(--scale-factor)*213.89px); top: calc(var(--scale-factor)*329.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.971992);" role="presentation">carried out to investigate the effect of spring stiffness on the ride comfort <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*342.41px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.961613);" role="presentation">considering a speed range of 10 km/hr – <span dir="ltr" style="left: calc(var(--scale-factor)*249.41px); top: calc(var(--scale-factor)*342.41px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.971619);" role="presentation">20 km/hr. The equations of the quarter car system are solved by <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*355.61px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.04159);" role="presentation">MATLAB a<span dir="ltr" style="left: calc(var(--scale-factor)*121.46px); top: calc(var(--scale-factor)*355.61px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.925836);" role="presentation">nd the behavior of the system with <span dir="ltr" style="left: calc(var(--scale-factor)*264.41px); top: calc(var(--scale-factor)*355.61px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.967478);" role="presentation">different spring stiff<span dir="ltr" style="left: calc(var(--scale-factor)*345.67px); top: calc(var(--scale-factor)*355.61px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.860094);" role="presentation">ness is <span dir="ltr" style="left: calc(var(--scale-factor)*375.19px); top: calc(var(--scale-factor)*355.61px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.920467);" role="presentation">analyzed with respect to its <span dir="ltr" style="left: calc(var(--scale-factor)*488.26px); top: calc(var(--scale-factor)*355.61px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.931328);" role="presentation">effect on <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*368.81px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.884539);" role="presentation">sprung mass displacement <span dir="ltr" style="left: calc(var(--scale-factor)*179.45px); top: calc(var(--scale-factor)*368.81px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.905641);" role="presentation">and Root Mean <span dir="ltr" style="left: calc(var(--scale-factor)*243.65px); top: calc(var(--scale-factor)*368.81px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.90901);" role="presentation">Square (RMS) <span dir="ltr" style="left: calc(var(--scale-factor)*304.27px); top: calc(var(--scale-factor)*368.81px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.89455);" role="presentation">value of the sprung mass displacement.